Aplikasi Modified Cassava Flour (MOCAF) Termodifikasi Heat Moisture Treatment (HMT) pada Pembuatan Kulit Wonton Gluten free - Dita Aulia Rahma (Fakultas Teknologi Pertanian, 2025)
Wonton wrappers are made using wheat flour as a base. However, the high level of gluten in wheat flour can be a problem. Gluten intake can aggravate liver disease, leading to increased inflammation and oxidative stress in the liver. MOCAF is different from wheat flour. MOCAF has high viscosity, low solubility, and expandability due to its lack of gluten and low protein content. However, application of MOCAF to wonton skin results in a product that is less rigit and tends to be brittle when processed or cooked. Heat Moisture Treatment (HMT) is a physical flour modification technique that can increase solubility, dough rise, and improve the functional properties of weak starch. MOCAF HMT is an alternative to improve dough characteristics that are less stable. The purpose of this study was to determine the effect of variation in the proportion of MOCAF HMT in making gluten free wonton skin on physicochemical characteristics, organoleptic, and to determine the best formulation through effectiveness test. This research method uses a completely randomized design (CRD) with a single factor, namely the substitution of MOCAF HMT with the formula KM0 (50% tapioca flour: 50% rice flour), KM1 (30% natural MOCAF: 35% tapioca flour: 35% rice flour), MP1 (30% natural MOCAF: 35% tapioca flour: 35% rice flour), MP2 (40% MOCAF HMT: 30% tapioca flour: 30% rice flour), MP3 (50% MOCAF HMT: 25% tapioca flour: 25% rice flour) MP4 (60% MOCAF HMT: 20% tapioca flour: 20% rice flour), MP5 (70% MOCAF HMT: 15% tapioca flour: 15% rice flour). The results showed that MOCAF HMT had a significant effect on moisture content, water absorption, cooking loss, brightness, texture, hedonic test, and effectiveness test
Reaploud Repository February_Hasyim
Keywords: MOCAF; High Moisture Treatment (HMT); Wonton wrapper/ Sheet; Gluten free